Parasites of Native and Invasive Rodents in Chile: Ecological and Human Health Needs - Landaeta-Aqueveque, Carlos; Moreno Salas, Lucila; Henríquez, AnaLía; Silva-de la Fuente, María C.; González-Acuña, Daniel (Frontiers in Veterinary Science, 2021)
Invasive populations are a threat to biodiversity, resulting in the loss of species, and also a threat to human health, participating in the reservoir of diseases. Rodents are among the most important invasive species worldwide. Chile is a country that features island conditions in terms of geography and has been widely invaded by allochthonous rodents. In this mini-review, we updated the literature on macro-parasites infecting both native and invasive rodents and of vector-borne pathogens in continental Chile in order to assess the relative importance of invasive rodents from both ecological and public health points of view. A total of 174 parasite species were found, with Siphonaptera representing the most diverse group. When examining how parasites are shared between native and introduced rodents, the analysis suggests that parasites circulate freely within recipient populations, and are not significantly transmitted from source populations. Further, generalist parasites are typically more prone to being shared between native and introduced rodents. Most zoonotic parasites were reported in invasive rodents, suggesting that these rodents must represent a public health concern. Although several vector-borne pathogens have been reported in rodents or ectoparasites, most of the recently emerging research has illustrated that there is a lack of evidence on rodent–vector-borne zoonoses in most pathogens.